Undetected Respiratory Depression in People with Opioid Use Disorder. (1st May 2022) - Tas, B.; Kalk, NJ; Lozano- García, M.; Rafferty, GF; Cho, PSP; Kelleher, M.; Moxham, J.; Strang, J.; Jolley, CJ
Abstract: Background: Opioid-related deaths are increasing globally. Respiratory complications of opioid use and underlying respiratory disease in people with Opioid Use Disorder (OUD) are potential contributory factors. Individual variation in susceptibility to overdose is, however, incompletely understood. This study investigated the prevalence of respiratory depression (RD) in OUD treatment and compared this to patients with chronic obstructive pulmonary disease (COPD) of equivalent severity. We also explored the contribution of opioid agonist treatment (OAT) dosage, and type, to the prevalence of RD. Methods: There were four groups of participants: 1) OUD plus COPD ('OUD-COPD', n = 13); 2) OUD without COPD ('OUD', n = 7); 3) opioid-naïve COPD patients ('COPD'n = 13); 4) healthy controls ('HC'n = 7). Physiological indices, including pulse oximetry (SpO2 %), end-tidal CO2 (ETCO2 ), transcutaneous CO2 (TcCO2 ), respiratory airflow and second intercostal space parasternal muscle electromyography (EMGpara ), were recorded continuously over 40 min whilst awake at rest. Significant RD was defined as: SpO2 %< 90% for > 10 s, ETCO2 per breath > 6.6 kPa, TcCO2 overall mean > 6 kPa, respiratory pauses > 10 s Results: At least one indicator was observed in every participant with OUD (n = 20). This compared to RD episode occurrence in only 2/7 HC and 2/13 COPD participants (p < 0.05, Fisher's exact test). The occurrence of RD was similar in OUD participants prescribed methadone (n = 6) compared to those prescribed buprenorphine (n = 12). Conclusions: Undetected RD is common in OUD cohorts receiving OAT and is significantly more severe than in opioid-naïve controls. RD can be assessed using simple objective measures. Further studies are required to determine the association between RD and overdose risk. Highlights: Respiratory depression was commonly observed among those receiving opioid substitution treatment. Severity of respiratory depression was greater in people on OST than opioid-naïve comparators. There were no differences in respiratory depression severity between methadone & buprenorphine. Respiratory depression can be undetected in routine drug treatment clinical care. Detection of respiratory depression can be obtained through simple measures.